Assessing On-Demand Delivery's Impact on Service Quality in South Africa's Construction Material Industry using SERVQUAL - Madiba , Sello (University of the Witwatersrand, Johannesburg, 2024)
The construction material industry is integral to economic growth, particularly in developing nations like South Africa. However, challenges in supply chain management (SCM), procurement inefficiencies, delivery services and evolving customer expectations necessitate the exploration of digital solutions. This study investigates the perceived impact of On-Demand Delivery (ODD) services on service quality (SQ) within South Africa’s construction material industry, using the SERVQUAL model. The research addresses a critical gap in understanding how digital delivery models affect service quality. The study is guided by the SERVQUAL framework, which evaluates five key service quality dimensions, viz, Tangibles, Reliability, Responsiveness, Assurance, and Empathy to determine their influence on ODD effectiveness in construction material supply chains. A quantitative research approach was employed, utilizing a structured questionnaire distributed via online platforms to a sample population of South African consumers engaged in construction projects over the past three years. Responses from 140 participants were analysed using Structural Equation Modelling (SEM) to assess the relationships between SERVQUAL constructs and overall service quality. Key findings indicate that Empathy (β = 0.702, p < 0.001) and Reliability (β = 0.428, p < 0.001) have the strongest positive impact on perceived service quality, suggesting that personalized service interactions and dependable delivery schedules significantly impacts service quality and ultimately enhances customer satisfaction and loyalty. Responsiveness (β = 0.335, p = 0.006) and Assurance (β = 0.143, p = 0.035) also contribute positively but to a lesser extent. Tangibles, while positively perceived, do not significantly impact overall service quality (p = 0.871). The study concludes that ODD services play a pivotal role in improving service quality in the construction material industry, with reliability, responsiveness, and empathy emerging as key drivers. The findings provide potential valuable insights iii for business owners, supply chain managers, and policymakers seeking to optimize digital logistics and customer-centric service strategies. Future research is recommended to explore regional variations, cost implications, and regulatory considerations in ODD adoption.
A research report submitted in fulfillment of the requirements for the Master of Management in the field of Digital Business, in the Faculty of Commerce Law and Management, Wits Business School, University of the Witwatersrand, Johannesburg, 2024
Keywords: UCTD; supply chain management (SCM); on-demand delivery (ODD); SERVQUAL; Structural Equation Model (SEM); SDG-9: Industry, innovation and infrastructure; SDG-8: Decent work and economic growth